Environmental Governance under Decentralization: A Comparative Legal Analysis - Shelvi Rusdiana; Hanifah Ghafila Romadona; Ampuan Situmeang; Mimi Sintia Mohd Bajury Bajury; Winda Fitri (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
Environmental governance in Southeast Asia continues to face serious challenges due to climate change, pollution, and the persistent tension between centralized authority and local autonomy. This study addresses the legal problem of whether decentralization frameworks in Indonesia, Thailand, and the Philippines adequately support environmental governance and the protection of the right to a healthy environment. The study aims to comparatively assess the normative structure of decentralization and environmental regulation in those three jurisdictions and to identify the legal implications of centralized tendencies within their governance systems. This research employs a doctrinal legal research method with a comparative approach, relying on primary legal sources and relevant secondary materials. The findings show that all three countries formally recognize local governmental roles in environmental management, yet substantial centralized control remains dominant. Indonesia and Thailand exhibit stronger top-down regulatory structures that constrain local autonomy, while the Philippines offers a relatively more participatory and comprehensive framework, though it remains highly fragmented. The study concludes that decentralization in ASEAN environmental governance has not yet fully ensured effective legal protection of the right to a healthy environment.